Peptidyl-prolyl Isomerase Pin1 Controls Down-regulation of Conventional Protein Kinase C Isozymes - Abrahamsen, Hilde (American Society for Biochemistry and Molecular Biology, 2012)
The down-regulation or cellular depletion of protein kinase C (PKC) attendant to prolonged activation by phorbol esters is a widely described property of this key family of signaling enzymes. However, neither the mechanism of down-regulation nor whether this mechanism occurs following stimulation by physiological agonists is known. Here we show that the peptidyl-prolyl isomerase Pin1 provides a timer for the lifetime of conventional PKC isozymes, converting the enzymes into a species that can be dephosphorylated and ubiquitinated following activation induced by either phorbol esters or natural agonists. The regulation by Pin1 requires both the catalytic activity of the isomerase and the presence of a Pro immediately following the phosphorylated Thr of the turn motif phosphorylation site, one of two C-terminal sites that is phosphorylated during the maturation of PKC isozymes. Furthermore, the second C-terminal phosphorylation site, the hydrophobic motif, docks Pin1 to PKC. Our data are consistent with a model in which Pin1 binds the hydrophobic motif of conventional PKC isozymes to catalyze the isomerization of the phospho-Thr-Pro peptide bond at the turn motif, thus converting these PKC isozymes into species that can be efficiently down-regulated following activation.